Relevansi Nilai Aset Dan Liabilitas Pajak Tangguhan - Cindy Melanie; Carmel Meiden (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
One of the accounting information that holds a major role for stakeholders is earnings information since it is considered could measure companies’ performance. However, the 2008 global economy crisis causes the earnings information became irrelevant to assess operational companies’ performance. This condition urges the investors to use other information, that is deferred tax information. Therefore, this research aims to test the effect of deferred tax assets and liabilities on stock prices. PSAK 46 states that deferred tax information denotes deferred tax income recoverable and income tax payable in the future which have to be presented in balance sheet. Deferred tax asset information is depicted to reflect a positive value in future company’s cash flow for the tax expense reduction, meanwhile deferred tax liabilities information reflects a negative value in future company’s cash flow because of the tax obligations that will arise in the future. The object of this research is manufacturing companies listed on Indonesia Stock Exchange in the 2011 – 2020 period. This research is using the judgment sampling method, consisting of 400 observation data. The coefficient determination shows that the dependent variable can be explained by the independent and control variables in the amount of 62%. Individually, the result of this research is that deferred tax assets have a significant positive effect on stock price, otherwise deferred tax liabilities have a significant negative effect. As a result, this study concludes that deferred tax assets and deferred tax liabilities have value relevance and this information can be used as a consideration by the investors in the making decision process.